WIND VARIATION FEATURES OF SYOWA AND ASUKA STATIONS, EAST ANTARCTICA - カネト, ススム; イガラシ, ヒロシ; マツハラ, カズマサ; KANETO, Susumu; IGARASHI, Hiroshi; MATSUHARA, Kazumasa (National Institute of Polar Research, 1994)
P(論文) Wind speed and direction at Syowa and Asuka Stations, East Antarctica have been analyzed. From monthly mean wind speed, Asuka was classified in the inland area type of J. INOUE (Nankyoku no Kagaku, 3. Kisho, ed. by Natl Inst. Polar Res., Tokyo, Kokon Shoin, 57,1988). To reveal diurnal variations of the two stations' winds, hourly wind data of the day, when the daily mean cloud amount was less than 5 in tenths, were selected to avoid the influence of large scale disturbances. Wind speed shows large diurnal variation at both stations on summer clear days but not on clear winter days. Prevailing wind direction at Syowa is NE and at Asuka is ESE. At Syowa, diurnal variation of wind direction is seen on clear summer days; a secondary direction appears on clear winter days. At Asuka on clear summer days, the variation of wind direction is small and the same as that of inland observations. departmental bulletin paper